Expanding the scope of free-radical dispersion polymerisation in supercritical carbon dioxide - McAllister, Thomas D (2017)
Electrophoretic displays (EPD) show several advantages over other display screen types including being easy on the eye, low power consumption, good visibility in bright daylight and a wide viewing angle. However, conventional EPDs only offer black and white images. One possible approach to colour EPD is the use of coloured particles. Here, the colours that can be displayed are dictated largely by the colour of the colloidal particles dispersed within the screen, which are traditionally carbon black and titanium dioxide white.